Odpowiedź :
Odpowiedź:
[tex]a)\ \ 6^2-4^2=36-16=20\\\\b)\ \ (2+5)^2=7^2=49\\\\c)\ \ 3^3-(-3)^3=27-(-27)=27+27=54\\\\d)\ \ 2^5\cdot6^0+2^2=32\cdot1+4=32+4=36\\\\e)\ \ 3\cdot4^2=3\cdot16=48\\\\f)\ \ 6^2+2^6=36+64=100\\\\g)\ \ 2^2+3^2+4^2=4+9+16=29\\\\h)\ \ 3^2\cdot(-1)^4-(-7)^0=9\cdot1-1=9-1=8[/tex]
[tex]a) 6^2-4^2=36-16=20\\b) (2+5)^2=7^2=49\\c) 3^3-(-3)^3=3^3+3^3=27+27=54\\d) 2^5*6^0+2^2=2^5*1+2^2=2^5+2^2=32+4=36\\e) 3*4^2=3*16=48\\f) 6^2+2^2=36+4=40\\g) 2^2+3^2+4^2=4+9+16=29\\h) 3^2-(-1)^4-(-7)^0=9-1-1=7[/tex]